Key oncogenes and candidate drugs for hepatitis-B-driven hepatocellular carcinoma progression - Liqin Ruan; Ningbo Fang; Xinhua Zhao; Weili Chen; Zhaoping Wu; Xiaoyong Wu (Discover Oncology)
Abstract Background This study aimed to uncover the key hepatitis-B (HB)-related liver cancer (LC) promoting genes, and clarity their interrelationships, enrichments, impacts on LC immune infiltration, and potential drugs targeting these genes. Methods The LC-survival associated genes were acquired from the LIHC samples of the TCGA-database; and HB related genes from the DisGeNET database. The intersection was used to screen the key genes. Using the 8 HB-LC genes, we constructed prognostic models for survival prediction of HBV positive patients with LIHC and performed enrichment analysis, interaction analysis, immune infiltration analysis, and potential drug digging from the GTRP and GDSC databases. Results In the core intersection of different sets. Based on these genes, prognostic cox regression models for OS and DFS were constructed. Overall, HB-LC genes were significantly negatively correlated with Th17, MAIT, monocytes, and CD4 Naive cells, while they were positively correlated with B cells, nTreg cells, and Tr1 cells. Among 8 genes, MKI67, EZH2, and CDCA5 were hub ones. Finally, 7 drugs target at least three HB-LC genes and can be used as novel drugs. Conclusions Together, eight key HB-LC genes play important cancer-promoting roles in LC, which may be the molecular mechanism by which HBV drives the development of LC.